ChemInform Abstract: Synthesis and Suzuki—Miyaura Cross‐Coupling of Enantioenriched Secondary Potassium β‐Trifluoroboratoamides: Catalytic, Asymmetric Conjugate Addition of Bisboronic Acid and Tetrakis(dimethylamino)diboron to α, β‐Unsaturated Carbonyl Compounds. Issue 16 (22nd April 2014) - Molander, Gary A.; Wisniewski, Steven R.; Hosseini‐Sarvari, Mona
Abstract Enantioenriched title compounds are synthesized via a new asymmetric, copper‐catalyzed addition of tetrahydroxydiboron to various α, β‐unsaturated amides, ketones, and esters in high yields and enantioselectivities.